Evaluasi strategi bauran pemasaran pada rumah makan marina hash in manado di masa pandemi covid-19 - Mariska Hakim (Universitas Sam Ratulangi, 2022)
Abstract: In achieving the right and effective marketing, one of them can refer to the marketing mix strategy. One of the marketing mix strategies that can be used to support the success of product marketing is to use the 7P method. This study aims (1) To determine the marketing mix strategy carried out by the Marina Hash Inn Manado Restaurant the Covid-19 Pandemic. (2) To determine the results of the evaluation of the marketing mix strategy at the Marina Hash In Manado Restaurant the Covid-19 Pandemic. The research method used is descriptive qualitative research, data collection using observation interview techniques with a sample of owners, employees and consumers of the Box Weal Manado restaurant. The results of this study indicate that the marketing mix strategy carried out by the Marina Hash Inn Manado Restaurant the Covid-19 Pandemic is good and after being evaluated is effective/in accordance with the marketing value.